(untitled) (Nóema, 2017)
The topic of this essay is the work of the reflection. After having focused on the «rift» between reflection (i.e., «seeing oneself») and its working in Valéry’s thought, Vitiello focuses on the process which Hegel described in The Phenomenology of Spirit, namely the process of the experience of the consciousness, which elevates itself to the consciousness of the experience. The conclusion is strongly critical: Hegel misses the aim at the very point in which he achieves it. Indeed, in the absolute knowledge, in the complete and perfect view of itself, of the light which sees the light, the experience of the consciousness itself fails, its becoming, its «imperfection» fail. The critique of Hegel, passing through Nietzsche, expands to a critique of language, in particular of the language of «being» and of «is», and of the Heideggerian tautologies, such as «das Ereignis ereignet», «das Ding dingt», «die Welt weltet». An important passage of the text concerns the theatrical language, in which the word seems to regain the original bond between voice and gesture, which remains divided nevertheless, because the medium itself which connects them – i.e., the «color» of the word – is «outside» the word and «outside» the gesture. Only the word of the act, of the pragmata, remains. In such a word, doing exhibits its most appropriate modality, namely the immediacy of being-affected: the cry of pain; or the reflexive mediacy of the moral imperative: Handle! The two opposite «colours» of the things.